Disorders of retina and vitreous - Khurana, AK; Sood, Sunandan; Kumar, Atul; Narang, Subina; Khurana, Aruj K. (Modern system of ophthalmology MSO series, 2014)
Modern System of Ophthalmology (MSO) is a series of multiple volumes, planned with a very specific aim to cater to the needs of residents in ophthalmology. The volume editors of this series make a team of like-minded and devoted teachers from different subspecialities. Disorders of Retina and Vitreous volume of MSO provides a comprehensive coverage on disorders of vitreous and retina in a concise manner. The text matter is complete and up-to-date with recent advances. It has been organised into six sections in an attractive colour format